KAJIAN HUKUM PENINGKATAN SERTIFIKAT HAK GUNA BANGUNAN MENJADI HAK MILIK DITINJAU DARI SURAT KEPUTUSAN GUBERNUR KEPALA DAERAH TINGKAT 1 KALIMANTAN TIMUR NOMOR 60 TAHUN 1990 TENTANG PENUNJUKAN DAN PENYERAHAN PENGUASAAN TANAH UNTUK MEMBANGUN PERUMAHAN PEGAWAI NEGERI DENGAN FASILITAS KPR-BTN DI LOA BAKUNG KECAMATAN SAMARINDA ULU KOTAMADYA SAMARINDA KEPADA PT. SEMANGGI SARANA REAL ESTATE (STUDI PADA PERUMAHAN KORPRI, LOA BAKUNG KOTA SAMARINDA) - Meiriana Meiriana; Yatini Yatini (Yuriska: Jurnal Ilmiah Hukum, 2016)
The Decree of the Governor as a first lauder in Bprneo No. 60 of 1990 February 13, 1990, on appointment and Transfer Tenure Land to Build Housing Servants with amenities KPR-BTN in Loa Bakung District of north Samarinda makes residents Housing KORPRI can’t do improvement of its original certificate certified Broking become Proprietary cases occurred in 2013 involving housing residents KORPRI Loa Bakung Samarinda apply for status change represented by the board to the Governor of Borneo Cq. Head of the Bureau of Supplies Regional Secretary by Statement of Claim number 845.1 / 284 / IV / 2013 dated 18 April 2013 in order to increase private property it is still no clarity and actions to date Throughout the absence of a decision or clarity by the Governor of East Kalimantan Cq. Head of the Bureau of Supplies Provincial Secretary east kalimantan and the National Land Agency (BPN) Samarinda, the improvement of the status of land rights in housing KORPRI Loa Bakung Samarinda City of Broking become right coupled with no standardization of fees to increase land rights of both the agency will be difficult to materialize.